Intelligent point of care test for food safety via a smartphone - Le Zhang; Xianglong Yang; Meijuan Liang; Zhiquan Tian; Zhaowei Zhang (Exploration of Foods and Foodomics)
The on-site, rapid, and intelligence detection methods are the wave in food safety. Recently, intelligent point-of-care test (iPOCT) methods serve as a promising alternative for advanced monitoring in food safety. By integrating smartphones with various detection methods, iPOCT methods demonstrate unique merits. Compared with lab-dependent instruments, iPOCT strategies have a short turnaround time (several minutes), high accuracy (μm level or less), and portability (smartphones). This work discussed principles of optical and electrical iPOCT methods, including absorbing light, fluorescence, chemiluminescence, potentiometry, voltammetry, impedance spectroscopy, and amperometry. The review emphasizes the practical applications for testing chemical and biological hazards in complex food matrices. The commercialization, challenges, and future trends of iPOCT are discussed as well.